Táticas de manejo do tripes do prateamento enneothrips flavens moulton em cultura de amendoim - Rosa, Matheus Elache [UNESP] (2014)
The peanut, Arachis hypogaea L., is a growing crop in Brazil and its current production is about 340 thousand tons, cultivated on an area of 102,3 thousand hectares. However, the yield is limited by the occurrence of pests and diseases and chemical control increases the cost of production. Among the various pests that attack the crop, the most important in Brazil is the silvering thrips Enneothrips flavens Moulton (Thysanoptera: Thripidae). The study aimed to evaluate, under field conditions, management tactics of silvering thrips E. flavens in peanut cultivar of creeping growth; phases of susceptibility peanut creeping growth habit of attack the silvering thrips E. flavens and its effects on productivity; and the effects of potassium fertilization on the population of the silvering thrips E. flavens cultured peanut creeping habit of growth. The three experiments installed in the agricultural years 2012/ 2013 were conducted in Fazenda de Ensino, Pesquisa e Extensão da Faculdade de Engenharia de Ilha Solteira-FE/UNESP, located in Selvíria, MS. In the first experiment was evaluated as management tactics, seed treatment; seed treatment + foliar spraying with 20%, 30% and 40% leaflets in the presence of at least one thrips, respectively; The method of producer (conventional) in the form of seed treatment insecticide + foliar sprays at 30, 45, 60, 75, 90 and 105 days after emergence of the plants; foliar spray insecticide with 30% of the leaflets with the presence of at least 1 and thrips, and control (lack of control). In the second experiment we assessed protection periods of the plants at 10-20 days; 10-30 days; 10-40 days; 10-50 days; 10-60 days; 10-70 days; 10-80 days; 10-90 days; 10-100 days; 20-100 days; 30-100 days; 40-100 days; 50-100 days; 60-100 days; 70-100 days after emergence; and control (lack of control), to characterize the phases of increased susceptibility of peanut, the creeping ...